The legislation actually reached consumers in proper disposal of batteries? - Lyrio, Carina Soares; Chaves, Gisele de Lorena Diniz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Given the damage to health and the environment caused by the improper disposal of cells and batteries, the requirements of CONAMA legislation N°. 401/2008 and criticisms to this legislation, this article identifies consumers’ knowledge about the need for an environmentally friendly disposal of cells and batteries and if that link actually performs its role in the r everse supply chain, discarding such products in the appropriate places. For this, a survey research was conducted in three capitals of southeastern Brazil. Despite the legal rule been in force for more than four years, the results highlight the lack of knowledge of cell and batteries consumers for disposal these wastes in an environmentally friendly manner. There are gaps to be filled, especially regarding the information sharing between all links of this channel.